EFEK KONSUMSI BERBAGAI JENIS MINYAK GORENG TERHADAP KETEBALAN TUNIKA INTIMA PADA TIKUS JANTAN STRAIN WISTAR - Witradharma, Tetes Wahyu (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
CVD has close relationship with nutrition and food. But the results of another study did not support the close relationship between saturated fat intake with blood lipid levels and risk of CVD. The aim is to determine the effect of various types of fried oil consumption to the thickness of tunica intima in male rats of wistar strain. This study was an experimental research. The sample were 25 rats based on inclusion and exclusion criteria. Treatment groups were separated and each given long chain saturated fatty acid (LCSFA) cow fat, medium chain saturated fatty acid (MCSFA) VCO, polyunsaturated fatty acid (PUFA) corn oil and monounsaturated fatty acid (MUFA) olive oil orally 2.5 ml/day for 2 months. Data were obtained include the sample characteristics and thickness of tunica intima. The highest mean of tunica intima thickness was corn oil 16385,61±1715,79 nm and the lowest olive oil 12075,97±2464,34 nm (p=0,033). This study shows that the harmful effects of SFA and the protective effects of UFA to the thickness of tunica intima need to be corrected because not all SFA is bad and UFA is good for health. It is therefore recommended to inform about foods are beneficial for health.